The Relationship of Consumer Preference, Value Creation, and Global Supply Chain in the Third Wave Coffee Business in Sumatera Utara, Indonesia - Lailan Tawila Berampu; Sirojuzilam Sirojuzilam; Sutarman Sutarman; Beby K.F Sembiring (International Journal of Supply Chain Management, 2019)
Abstract— The third wave of the coffee era has a significant impact on increasing the coffee drinkers in Sumatera Utara. It saw from the ease of finding local coffee shops in this area. Therefore, the higher levels of competition made much local coffee shops in Sumatera Utara facing a high rate of failure. One reason many local coffee shops fail to manage their stores in the long run is that, local coffee shops in Sumatera Utara do not yet understand the preferences of coffee drinkers in the third wave coffee era. This study focuses on how the coffee business trend in the third wave era can be enhanced through preference and value creation based on Global Supply Chain and consumer preference as theoretical background. This study utilizes non-probability sampling and there 97 coffee shop owners were participated. The result of this study showed that value creation has a significant effect on the Global Supply Chain, value creation has no significant effect on preference. Value creation has a significant effect on Global Supply Chain through consumer preference in the third wave coffee business in Sumatera Utara. This study can be helping business consumers in Sumatera Utara to understand the factors of consumer preferences and create unique values for each coffee shop to gain competitive advantages.